Penerapan Sistem Informasi Manajemen (SIM) dalam Penjaminan Mutu Pembiayaan Pendidikan di Dayah Madinatuddiniyah Jabal Nur Paloh Lada Aceh Utara - Arham Bunaiya; Ikhsan Ikhsan (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2024)
This study aims to describe the application of the Management Information System (MIS) in quality assurance of education financing at Dayah Madinatuddiniyah Jabal Nur Paloh Lada. The method used is a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation. The data obtained was analyzed using the Miles and Huberman model, which includes data condensation, data presentation, and conclusion drawing. The results showed that the implementation of SIM through the Finanza application has succeeded in improving efficiency, transparency, and accountability in pesantren financial management. Nonetheless, challenges faced include limited trained human resources, limited technological infrastructure, resistance to change, as well as difficulties in customizing the system to the specific needs of the pesantren. The recommendation of this study is the need for increased HR training, strengthening technological infrastructure, and managing change to overcome these obstacles, so that SIM can make a greater contribution to improving the quality of education and financial management of pesantren.